ANALYSIS OF PACKAGING DESIGN BY INCREASING SALES TURNOVER IN THE PERSPECTIVE OF SHARIA ECONOMICS (STUDY ON UTTON OUTLET JL. GENERAL SUDIRMAN OF BONE REGENCY) - RIJAL, SYAMSUL; SAHAKA, ARIFIN; HASBI, HARTAS (Institut Agama Islam Negeri (IAIN) Bone, 2025)
Analysis of Packaging Design by Increasing Sales Turnover in a Sharia Economic Perspective. This research aims to find out whether product packaging design can increase sales turnover and whether product packaging design can increase sales turnover from an Islamic economic perspective at the UTTON Store Jl. Jendral Sudirman District. Bone The type of research used in this research is field research because the researcher conducted research directly at the UTTON Outlet, Bone Regency. The data collection techniques used in this research are interviews, observation and documentation. The instruments in the research carried out in this research were interview sheets and documentation sheets. The data analysis techniques used in this research are data reduction, data presentation, verification and drawing conclusions, and the validity of using member checking. The research results show that packaging design increases sales turnover at UTTON Outlets Jl. Jendral Sudirman District. Bone provides packaging that is futuristic in nature and has a contemporary feel, thus increasing customer or customer attraction in addition to the service and taste of the product itself. Islamic economic perspective in increasing sales turnover at the UTTON Outlet Jl. Jendral Sudirman District. Bone by applying the importance of benefit, fairness, simplicity, justice. By applying these principles, packaging design can reflect Islamic values in increasing sales turnover.